Asian Tiger’s economic progression and Influence of Sectoral FDI - Zahid, GulRukh; Nasir, Hamna; Ahmad, Mohsin Hasnain (Pakistan Journal of Humanities and Social Sciences, 2022)
In this paper, we scrutinize the sectoral FDI's influence on economic progression over the period of 2006-2015(the case study of Asian Tigers: (Hong Kong, Singapore, and Taiwan). The outcomes of the paper recommend that sectoral FDI has an affirmative and noteworthy influence on the economic progression of Asian Tigers. In light of our findings we suggest, to avail the fruits of economic growth through FDI, developing countries should invest more in human capital and improve financial openness.